Inspired by the work of Olivier Oloa [1] and the question of Vladimir Reshetnikov in a comment I succeeded in calculating the closed form of the sum

$$s_m = \sum _{k=1}^{\infty } \frac{\left(H_k\right){}^m-(\log (k)+\gamma )^m}{k}\tag{1}$$

for $m=3$.

The cases known (to me) are

$$s_1 = -\gamma _1+\frac{\pi ^2}{12}-\frac{\gamma ^2}{2}= 0.728694...\tag{2a}$$

$$s_2 = -2 \gamma \gamma _1-\gamma _2+\frac{5 \zeta (3)}{3}-\frac{2 \gamma ^3}{3}= 1.96897 ...\tag{2b}$$

$$s_3 =-3 \gamma ^2 \gamma _1-3 \gamma \gamma _2-\gamma _3+\frac{43 \pi ^4}{720}-\frac{3 \gamma ^4}{4}=5.82174 ...\tag{2c}$$

Here $\gamma$ is Euler's gamma, and $\gamma_k$ is Stieltjes gamma of order k.

Notice that $s_2$ was calculated in [1]. For a check of my method I calculated all three cases.

Inspecting the available cases $m=1, 2, 3$ I tentatively propose here a general formula for the closed form of $s_m$.

$$ s_{m}= -m \sum _{j=1}^{m-1} \gamma ^j \gamma _{m-j}+a_m \zeta (m+1)-\gamma _m-\frac{m }{m+1}\gamma ^{m+1}\tag{3}$$

Here the coefficients are

$$a_1=\frac{1}{2},\; a_2=\frac{5}{3},\; a_3=\frac{43}{8}\tag{4}$$

With only three terms of $a_k$ OEIS [2] returns of course too many choices to be able to identify the sequences. And what's more, I don't know if the true sequence is contained in OEIS at all.

Unfortunately, I could not extend my method to $m=4$.


  1. Prove the formula for $s(3)$

  2. Calculate $s(4)$ and verify and try to complete (3)


[1] A closed form of the series $\sum_{n=1}^{\infty} \frac{H_n^2-(\gamma + \ln n)^2}{n}$

[2] https://oeis.org/


Before showing my solution of the specific problem, I would like to make some remarks on useful methods.


To begin with, I describe briefly some methods to solve the following basic problem:

Given a sequence of numbers $a_k, k=1,2,3,...$ we wish to calculate the infinite sum $s=\sum_{k=1}^\infty a_k$.

To my knowledge there are three important methods to tackle the problem. The first two of which have been employed frequently here. I haven't yet seen the third method, which I have used here.

  1. Limit of partial sums

Maybe the most natural method as it employs just the definition of an infinite sum.

Defining the partial sum as $s_n = \sum_{k=1}^n a_k$ we have

$$s = \lim_{n\to \infty } \, s_n$$

  1. Integral representation

If the summand can be written as

$$a_k = \int_{0}^1 w(x,k) \, dx$$

with some function $w(x,k)$ then, interchanging sum and integral, we get

$$s = \int_{0}^1 W(x) \, dx$$


$$W(x) = \sum_{k=1}^\infty w(k,x)$$

  1. Generating function

Here we form a function $g(x)$ by multiplying the $a_k$ by $x^k$ ("wrapping") an summing up:

$$g(x) =\sum_{k=1}^\infty x^k a_k$$

This hopefully results in a known function, called the generating function (g.f) of the $a_k$.

Then we have

$$s = \lim_{x\to 1 } \, g(x)$$

We also obtain immediately an expression for the alternating sum defined as

$$s_a = \sum_{k=1}^\infty (-1)^k a_k$$


$$s_a = \lim_{x\to -1 } \, g(x)$$

Interchanging limits must be justified, of course. But here we skip this labour as we are just looking for a heuristic tool to find a closed expression. Once we have it, we can verify its validity numerically.

More specifically, the generating function method will be applied to cases where $a_k = u_k - v_k$ and where the sums of $u_k$ and $v_k$ separately can be divergent.

Despite of the separate divergence, in many cases their generating functions exist separately (the factor $x^k$ "forces" convergence) and we have

$$g(x) = g_u(x) - g_v(x)$$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.